Coevolution and coexistence of cooperation and competition in interorganizational collaboration: Evidences from Indian management consulting industry. (20th February 2017) - Panda, Debadutta Kumar
Abstract : Purpose: This study aims to understand the coevolution and coexistence of cooperation and competition in the interorganizational collaboration of management consulting firms (MCFs) in India. Design/methodology/approach: The narrative inquiry method was applied to understand the central phenomenon. The narrative inquiry method was found pertinent because the aim of the research was to inquire human-based phenomenon, especially life experiences, tensions, feeling, thought processes, emotions and personal puzzles. Narrations from 47 respondents from 32 MCFs from various consortiums were collected to make textual and phenomenal narrative inquiry. Finally, causal relationships were designed using the mapping method. Findings: The study noticed coevolution and coexistence of cooperation and competition in the MCF consortiums. Cooperation was higher than the competition at the entry level, and the competition was higher than cooperation at the operational level of the consortium life cycle. Organizational side of coopetition was higher than human side of coopetition at the entry level, and human side of coopetition was higher than organizational side of coopetition at the operational level. A higher level of competition (than cooperation) pushes the consortium beyond the threshold level, creating a lesser value creation. Further higher level of competition (than cooperation) shoved the consortium beyond the injury limit, leading the consortium to collapse. Research limitations/implications: This study paid major attention on the human side and organizational side of coopetition from the life cycle perspective, but the findings and discussions concentrated more on entry level and operational level. The study, in fact, did not capture the status of coopetition at the termination phase of the consortium. Originality/value: This study is one of the few studies that examined cooperation and competition as a single construct in interorganizational collaboration in the management consulting industry. This study is unique in two ways, one, examination from the human side of coopetition and organizational side of coopetition, and two, life cycle analysis of the consortium from the perspective of coopetition.